Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Luttes, oppressions, rapports sociaux de sexe - Descarries, Francine; Poulin, Richard (Ecosociété, 2010)
Bien que l’oppression des femmes soit antérieure au capitalisme, il n’en reste pas moins que ce mode de production lui a imprimé des spécificités. En outre, les femmes sont touchées de manière différente des hommes par la mondialisation néolibérale. Les rapports sociaux de sexe font partie des fondations et de l’agencement de ce capitalisme financiarisé, lequel a exacerbé la division sexuelle du travail. Ces rapports nous permettent de comprendre des phénomènes internationaux aussi important que la marchandisation du vivant (entre autres, du corps et du sexe), les mouvements migratoires, qui se sont féminisés, les nouvelles pauvretés, les hiérarchies sociales (caste, classe, groupes racialisés et ethnicisés), les violences, etc. Les femmes sont à la fois une main-d’oeuvre capitale tant pour le travail salarié que pour celui qui est non rémunéré, une source formidable de profits pour les entreprises et de travail gratuit pour la société dans son ensemble et pour les hommes en particulier. En même temps, grâce à cette position subordonnée dans la société et à la surexploitation qui en découle, les femmes constituent un groupe très actif tant dans l’analyse du monde actuel que dans les luttes et dans la mise en place d’alternatives. Sans cette perspective analytique, tout reste obscur. Pour les Nouveaux Cahiers du socialisme, les questions de l’oppression des femmes et du féminisme sont fondamentales. On ne peut imaginer penser et construire une alternative au capitalisme sans s’attaquer au patriarcat. Notre dossier est divisé en quatre parties. La première se penche sur différents enjeux politiques et théoriques, tant par rapport au socialisme marxiste qu’à l’intérieur du féminisme. La deuxième concerne quelques questions québécoises, dont la lutte du Front commun intersyndical, l’impact des politiques néolibérales sur la main-d’oeuvre féminine, les effets de ces politiques dans les domaines de la santé et de l’éducation en rapport avec la dégradation de la condition des femmes et la question des différences salariales et la lutte pour l’équité salariale. La troisième examine la masculinité, ses violences, son hégémonie. La quatrième fait état des luttes tant par les organisations autonomes des femmes que par celles qui sont mixtes et discute du Nous féministe.
Section: 1 vol. (294 p.) ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; amériques; anticapitalisme; approches et analyses; cours; fem1000; histoire et politique; justice sociale; militance; mouvements féministes; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques

Realizing the UN Declaration on the Rights of Indigenous Peoples: triumph, hope, and action - Joffe, Paul; Hartley, Jackie; Preston, Jennifer (Purich Pub., 2010)
Adopted by the UN General Assembly on 13 September 2007, the United Nations Declaration on the Rights of Indigenous Peoples affirms the “minimum standards for the survival, dignity and well-being of the indigenous peoples of the world.” The Declaration responds to past and ongoing injustices suffered by Indigenous peoples worldwide. It provides a strong foundation for improved relationships with states, and for the full recognition of the inherent rights of Indigenous peoples. Despite this, Canada was one of the few countries to oppose the Declaration. The contributors to this collection analyze the development of the Declaration, recall the triumph of its adoption, and illustrate the hopes and actions for its implementation. The discussion moves beyond Canadian borders to the international stage, providing accessible information and guidance on the Declaration and how it can be used to advance human rights. Policy makers, Indigenous communities, politicians, academics, lawyers, human rights advocates, NGOs, and anyone interested in the significance of the Declaration will find this to be a valuable resource. Contributors include Indigenous leaders, legal scholars and practitioners, state representatives, and representatives from NGOs, with extensive knowledge of and experience in Indigenous peoples’ human rights law, policy, and practice.
Le texte de McKay, M. C. et Benjamin, C. (2010). A vision for fulfilling the indivisible rights of Indigenous women a été donné en lecture au cours POL4105.
Keywords: 2000 à aujourd'hui; 2000-2009; ONU; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; droits des personnes autochtones; histoire et politique; justice sociale; pol4105; premier cycle; premiers peuples; premières nations; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Note de l’éditeur Traduit de l’anglais. Texte original: Under Western eyes : Feminist scholarship and colonial discourses. In Feminism without borders : Decolonizing theory, practicing solidarity. 17-42. Durham : Duke University Press. 2003. Tous droits réservés. Reproduit avec l’aimable autorisation de l’éditeur. Parution originale 1986.
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Pour une meilleure compréhension des particularités de la violence familiale vécue par les femmes autochtones au Canada - Montminy, Lyse; Brassard, Renée; Jaccoud, Mylène; Harper, Elizabeth; Bousquet, Marie-Pierre; Leroux, Shanie (Nouvelles pratiques sociales, 2010)
La violence conjugale en milieu autochtone présente des particularités qui demeurent trop souvent ignorées ou confondues avec celles d’autres groupes de femmes violentées au Canada. Cet article rapporte les résultats d’une analyse de documents produits au cours des trois dernières décennies afin de dégager les principales caractéristiques de cette problématique. Cette analyse suggère que la notion de violence familiale doit être privilégiée à toute autre et que la violence conjugale dont les femmes autochtones sont victimes se distingue tant par ses formes, sa fréquence que par sa gravité.Aspects that are unique to conjugal violence as experienced by Aboriginal women are often ignored and confounded with those of other groups of abused women in Canada. This article presents an analysis of documents from different sources of knowledge that have been produced over the last three decades in order to identify distinctive dimensions of this problem. The analysis points to the significance of the notion of family violence over other terms that are used to describe conjugal violence and to the different facets of Aboriginal women’s experiences of violence with regards to prevalence, severity and forms of violence.
Keywords: amériques; analyse documentaire; approches et analyses; canada; cours; discipline; femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; travail social; trs3500; violences; violences conjugales

Les termes du débat féministe - Van Enis, Nicole (Barricade asbl, 2010)
Les courants féministes sont divers. Dans cette étude, nous tentons de comprendre les enjeux du débat féministe, les revendications pour lesquelles les femmes se battent et les stratégies d’actions mises en place pour changer la vie des femmes.
Donné en lecture cours FEM1000: p.5-7; 11-18; 20 et 22
Keywords: 1900-1999; approches et analyses; cours; fem1000; histoire et politique; international; justice sociale; mouvements féministes; premier cycle; périodes historiques; ressource en ligne; thématiques; théories féministes

Le genre d’une migration post-coloniale : de Meknès (Maroc) à Montréal (Québec) - Yolande Cohen (Genre & Histoire, 2010)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afrique; afrique du nord; amériques; approches et analyses; canada; cours; discipline; ethnographie; france; his4830; histoire; histoire du féminisme; histoire et politique; immigration; justice sociale; maghreb; maroc; migration; militance; mouvements des femmes*; mouvements féministes; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques